Phytochemical analysis, antioxidant, antimicrobial, and anti-enzymatic properties of Alpinia coriandriodora (sweet ginger) rhizome - Wu, Xia; Wei, Feng; Ding, Furong; Yang, Nian; Niu, Jingming; Ran, Yuanquan; Tian, Minyi (Frontiers in Plant Science, 2023)
Alpinia coriandriodora, also known as sweet ginger, is a medicinal and edible plant. A. coriandriodora rhizome is popularly utilized in traditional Chinese medicine and as flavouring spices, but there are few reports on its constituents and bioactivities. This study analyzed the phytochemical components of A. coriandriodora rhizome by GC-MS and UHPLC-Q-Orbitrap-MS and evaluated its antioxidant, antimicrobial, and anti-enzymatic properties. According to the GC-FID/MS data, its rhizome essential oil (EO) consisted mainly of (E)-2-decenal (53.8%), (E)-2-decenyl acetate (24.4%), (Z)-3-dodecenyl acetate (3.5%), and (E)-2-octenal (3.5%). Its water extract (WE) and 70% ethanol extract (EE) showed high total phenolic content (TPC, 52.99-60.49 mg GAEs/g extract) and total flavonoid content (TFC, 260.69-286.42 mg REs/g extract). In addition, the phytochemicals of WE and EE were further characterized using UHPLC-Q-Orbitrap-MS, and a total of sixty-three compounds were identified, including fourteen phenolic components and twenty-three flavonoid compounds. In the antioxidant assay, WE and EE revealed a potent scavenging effect on DPPH (IC 50 : 6.59 ± 0.88 mg/mL and 17.70 ± 1.15 mg/mL, respectively), surpassing the BHT (IC 50 : 21.83 ± 0.89 mg/mL). For the antimicrobial activities, EO displayed excellent antibacterial capabilities against Proteus vulgaris, Enterococcus faecalis, Bacillus subtilis, Escherichia coli, and Staphylococcus aureus with DIZ (12.60-22.17 mm), MIC (0.78-1.56 mg/mL), and MBC (3.13 mg/mL) and significantly inhibited Aspergillus flavus growth (MIC = 0.313 mg/mL, MFC = 0.625 mg/mL, respectively). In addition to weak tyrosinase and cholinesterase inhibition, EE and WE had a prominent inhibitory effect against α-glucosidase (IC 50 : 0.013 ± 0.001 mg/mL and 0.017 ± 0.002 mg/mL), which was significantly higher than acarbose (IC 50 : 0.22 ± 0.01 mg/mL). Hence, the rhizome of A. coriandriodora has excellent potential for utilization in the pharmaceutical and food fields as a source of bioactive substances.